KLASIFIKASI KEPUASAN KUNJUNGAN MAHASISWA TERHADAP PERPUSTAKAAN MENGGUNAKAN METODE FUZZY SUGENO - Reza Fahlevi; Khairul Saleh (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
The assessment of student visit satisfaction at the Asahan University library is currently influenced by various uncertainty factors from each individual, making it difficult to measure objectively using the existing system. This study aims to build a more measurable classification system using the Fuzzy Sugeno logic method. The system is evaluated using four input parameters with a value range of 0 to 100, namely service quality, facilities, environmental comfort, and ease of information access, to generate an output variable divided into dissatisfied, satisfied, and very satisfied categories. Based on the test results, inputting a service quality value of 85, facilities 85, environmental comfort 55, and ease of information access 55 produced a recommendation value of 54.285, which was successfully classified linguistically into the "Satisfied" category. The application of the Fuzzy Sugeno method is proven to provide an accurate assessment, which is expected to assist library management in evaluating services and making strategic decisions for future quality improvements.